Meeting of nine oil-countries resolves to suspend the oil boycot of the Netherlands in Cairo. Place of the persons on the back of the photo
Meeting of nine oil-countries resolves to suspend the oil boycot of the Netherlands in Cairo. Place of the persons on the back of the photo.